2021
DOI: 10.1186/s13052-021-01049-w
|View full text |Cite
|
Sign up to set email alerts
|

Child Caregiver’s healthcare seeking behavior and its determinants for common childhood illnesses in Addis Ababa, Ethiopia: a community-based study

Abstract: Background Appropriate healthcare-seeking behavior and access to the health care facility is key to improving health service utilization. Although the accessibility of comprehensive childhood disease intervention services in Ethiopia has been modified at the community level, the use of such health care services has remained limited. Therefore, this study aimed to assess the healthcare-seeking behavior of common childhood illness and its determinants. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
8
1
1
Order By: Relevance
“…Based on the study setting, three of the studies were conducted in Addis Ababa [ 11 , 17 , 21 ], two in the Tigray region [ 18 , 42 ], seven in the Amhara region [ 20 , 22 , 23 , 25 27 , 37 ], seven in the Oromia region [ 15 , 32 – 35 , 38 , 43 ], one in the SNNP region [ 24 ], one in the Benishangul region [ 39 ], and four were conducted nationwide [ 16 , 36 , 40 , 41 ]. Regarding the illness category, fifteen studies were conducted by including all the three childhood diarrhea, fever, and respiratory tract infections at the same time [ 15 , 17 , 20 – 25 , 27 , 32 , 33 , 36 38 , 42 ], four were for diarrhea only [ 18 , 21 , 26 , 43 ], three were for fever only [ 34 , 35 , 39 ], and three were for ARI only [ 16 , 40 , 41 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the study setting, three of the studies were conducted in Addis Ababa [ 11 , 17 , 21 ], two in the Tigray region [ 18 , 42 ], seven in the Amhara region [ 20 , 22 , 23 , 25 27 , 37 ], seven in the Oromia region [ 15 , 32 – 35 , 38 , 43 ], one in the SNNP region [ 24 ], one in the Benishangul region [ 39 ], and four were conducted nationwide [ 16 , 36 , 40 , 41 ]. Regarding the illness category, fifteen studies were conducted by including all the three childhood diarrhea, fever, and respiratory tract infections at the same time [ 15 , 17 , 20 – 25 , 27 , 32 , 33 , 36 38 , 42 ], four were for diarrhea only [ 18 , 21 , 26 , 43 ], three were for fever only [ 34 , 35 , 39 ], and three were for ARI only [ 16 , 40 , 41 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 25 studies, 19 have factors associated with mothers' health-seeking behavior. Twelve studies identified factors for three illnesses [ 11 , 15 , 17 , 19 , 20 , 23 25 , 27 , 36 38 ], four for diarrhea [ 18 , 21 , 26 , 43 ], two for fever [ 35 , 39 ], and one for ARI [ 16 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations